PENGUKURAN KINERJA DOSEN MELALUI EKD (EVALUASI KINERJA DOSEN) STKIP PGRI SITUBONDO BERDASARKAN PERSEPSI MAHASISWA - John Harisantoso (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), 2012)
The aim of this research was to evaluate faculty performance in STKIP PGRI Situbondo based on the perception of students as the first item. A second detecting weaknesses in faculty performance point STKIP PGRI Situbondo. This research method is the census because the object of study includes all students in STKIP PGRI Situbondo. The study was a descriptive research is descriptive quantitative instruments backed by descriptive statistics. Primary data was explored by a questionnaire and tabulation using the Likert scale from 1 for very poor performance to score 5 for best performance. Secondary data was collected from the literature relevant to the purpose of research. Analytical instruments including the relative frequency, cumulative frequency, aritmethic mean and standard deviation. All instruments are supported by means of SPSS in analyzing the menu Analyze Descriptive Tabulation of Frequency and summary Reports in the column. The analysis showed that the performance of lecturers in four competencies include pedagogic competence, professional, personal and social development can be said to be good overall. Nevertheless, based on student perceptions of discipline and compliance issues as well as control of media and instructional technology professors also need to be improved, especially in the use of existing facilities. Keywords: Lecturer’s performance, strongs and weaknesses.